THU0660 CHARACTERIZATION OF SCLERODERMA PATIENTS ACCORDING TO RO52 AND KU ANTIBODIES. (June 2019) - Castro, Julien Caballero; Castillo, Alfredo Guillén del; Callejas-Moraga, L. Eduardo; Argüelles, Dolores Colunga; Sáez-Comet, Luis; Rubio-Rivas, Manuel; Argibay, Ana; Vargas-Hitos, Jose Antonio; Parra, Jose Antonio Todolí; Fraile, Isabel Perales; Simeón-Aznar, Carmen Pilar; ,; et al.
Abstract : Background: Systemic Sclerosis (SSc) is an autoimmune desease that is characterized by progressive and severe fibrosis with cutaneous and visceral involvement, fibroproliferative vasculopathy and alterations of cellular and humoral immunity, very heterogenous from the clinical and immunological point of view. There are many types of antibodies related to the disease that are used in the diagnosis and characterization. Antibodies anti-Ku and anti-Ro52 have been found, although they are not specific to the disease, that could play an important role in the prognosis and clinical expression. Objectives: To evaluate the clinical pattern and prognosis of SSc patients who carry antibodies Anti-Ku and Anti-Ro52. Methods: A retrospective, multicentric study of SSc patients included in the Spanish Registry of Scleroderma (RESCLE). Clinical, demographic, prevalence, serological, and survival data were analyzed Results: A total of 401 samples were analyzed for anti-Ku with 12 positive results (3%). For anti-R052, 1724 sampled were analyzed with 246 positive results (14%). It is observed, from the multivariant analysis, that patients with anti-Ro52 presented, in higher frequency, an association with Sicca syndrome (p<0.001) and its coexistence with the antibody anti-La (OR 44.8 with 95% CI and p<0.001). Regarding patients with anti-Ku, no clinical association was found with statistical significance. Conclusion: As opposed to finding SSc specific antinbodies such as anti-centromere (ACA), anti-topoisomerase I (ATA), and anti-RNA polymerase III (ARA), the presence of anti-Ku or anti-Ro52 is not conclusive of any distinctive clinical profile. References: [1] Mehra S., et al. Autoantibodies in systemic sclerosis. Autoinmunity Reviews 2013; 12:340-354. [2] Stern E., Denton C. The Pathogenesis of systemic Sclerosis. Rheum Dis Clin North Am 2015; 41(3):367-82. [3] Cavazzana I., et al. A subset of systemic sclerosis but not of systemic lupus erythematosus is defined by isolated anti-Ku autoantibodies. Clin Exp Rheumatology 2013; 31:118-21. [4] Iniesta N.; et al. Influence of antibody profile in clinical features and prognosis in a cohort of Spanish patients with systemic sclerosis. Clin Exp Rheumatology 2017; 35(suppl. 106)S00-S00. Disclosure of Interests: None declared